The Potential of Tajwid Lake Tourism Development in Langgam Riau - M Rawa El Amady; Anggi Arrahman; Amru Mahalli (Budapest International Research and Critics University, 2022)
This study discussed the tourism of Lake Tajwid in Langgam Village, Langgam District, Pelalawan Regency, Riau. This destination has its own uniqueness because it was built by the Pelalawan Regency government from the customary land of the Domo tribe, and combines natural, cultural tourism with modern rides. This tour manager has not implemented community-based tourism even though its position is in the midst of people who come from customary lands. To conduct this study, the author uses a qualitative method with an ethnographic design. The author stayed at the research location for two months, conducting involved observations and in-depth interviews with informants consisting of community leaders, tourism managers and the wider community. This study found that this tour has a unique characteristic compared to other tourist destinations in Pelalawan Regency, and this tour has been able to contribute to local revenue (PAD). However, this tourist destination has not implemented community-based tourism so that a latent conflict has been found which if the Tajwid Lake tourism manager does not respond immediately, it will open up the possibility of open conflict. Tajwid Lake tourism has the potential to be developed, especially nature tourism and cultural tourism to meet the needs of the working class who work around the Tajwid Lake tourist area. This study contributes to tourism anthropology and the results can be used by tourism managers and the Pelalawan district government and become initial information for researchers who will carry out the same research and in the same place.